QOLP-27. CLINICAL FACTORS AND MOLECULAR MARKERS ASSOCIATED WITH POSTOPERATIVE SEIZURES IN GLIOBLASTOMA. (11th November 2019) - Chandra, Ankush; Kanungo, Ishan; Rick, Jonathan; Yue, John; Dayani, Fara; Nguyen, Alan; Flanigan, Patrick; Chang, Edward; McDermott, Mike; Berger, Mitchel; Aghi, Manish
Abstract: INTRODUCTION: Glioblastoma has a poor prognosis, further complicated by postoperative seizures. We analyzed various factors associated with postoperative seizures in glioblastoma. METHODS: Retrospective chart review of 932 patients who underwent craniotomy for glioblastoma (777=83.4% newly diagnosed; 155=16.6% recurrent) at our institution (2002–2014). Postoperative seizures were defined as those occurring within 14 days of surgery. RESULTS: Our cohort consisted of 49.9% (n=465) males with mean age of 55.8 (range 9–91) years. In total, 69 (7.4%) had postoperative seizures with mean time from surgery to seizure of 3.1 days (IQR=1–4). Of 536 patients (57.5%) receiving seizure prophylaxis, those treated with Keppra were more likely to have postoperative seizures compared to those on Dilantin (10.9% vs 5.0%; p=0.022). Primary tumor patients were less likely to seize postoperatively compared to recurrent tumor patients (9.7% vs 19%; p=0.016). Patients presenting with seizure as chief complaint (12.1% vs 5.1%; p=0.025) and those with >20% of Chromosome 10 deletion were more likely to have seizures postoperatively (12.4% vs 6.1%; p=0.0029). Risk factors for postop seizures for newly-diagnosed patients included subtotal resection versus gross total resection (28.0% vs 7.1%; p=0.022). Risk factors for postop seizures for recurrent patients were >5% EGFR amplification (23.5% vs 5.8%; p=0.0021) and hyponatremia within mean 2.5 days (IQR 0–1) after surgery (20.8% vs 7.1%; p=0.035). CONCLUSION: We identified several risk factors for postoperative seizures in glioblastoma patients, most of which were clinical (seizure as chief complaint, the antiepileptic chosen for prophylaxis, and extent of resection), while some were molecular and linked to genes whose products have demonstrated links to epileptogeneicity (Chromosome 10, EGFR). These findings may assist physicians in detecting glioblastoma patients that are at higher risk for postoperative seizures and in providing prophylaxis to reduce morbidity.